The RISE trial: A Randomized Trial on Intra-Saccular Endobridge devices. Issue 1 (February 2020) - Raymond, Jean; Januel, Anne-Christine; Iancu, Daniela; Roy, Daniel; Weill, Alain; Carlson, Andrew; Darsaut, Tim E
Background: Wide-necked bifurcation aneurysms (WNBA) are a difficult subset of aneurysms to successfully repair endovascularly, and a number of treatment adjuncts have been designed to improve on the results of coiling, including stenting and flow diversion of the parent vessel. Surgical clipping is commonly performed for certain WNBAs, such as middle cerebral aneurysms, in some centres. Intra-saccular flow diversion (ISFD) using the Woven Endo-Bridge (WEB) or similar devices, has been developed as a new endovascular alternative to coiling for WNBAs. Meta-analyses of case series suggest satisfactory results, both in terms of safety and efficacy, but in the absence of randomized evidence, whether ISFD leads to better outcomes for patients with WNBA remains unknown. There is a need to offer ISFD within the context of a randomized care trial. Methods: The proposed trial is a multicentre, randomized controlled care trial comparing ISFD and best conventional management option (surgical or endovascular), as determined by the treating physician prior to randomized allocation. At least 250 patients will be recruited in at least 10 centres over a four-year period, and followed for one year, to show that ISFD can increase the incidence of successful therapy from 75 to 90% of patients, defined as complete or near-complete occlusion of the aneurysm AND a good clinical outcome (mRS ≤ 2) at one year. The trial will be followed by an independent data safety monitoring committee to assure the safety of participants. Conclusion: Introduction of intra-saccular flow diversion can be accomplished within a care trial context.